2015
DOI: 10.1021/acs.est.5b01203
|View full text |Cite
|
Sign up to set email alerts
|

Hybrid-Electric Passenger Car Carbon Dioxide and Fuel Consumption Benefits Based on Real-World Driving

Abstract: Hybrid-electric vehicles (HEVs) have lower fuel consumption and carbon dioxide (CO2) emissions than conventional vehicles (CVs), on average, based on laboratory tests, but there is a paucity of real-world, on-road HEV emissions and performance data needed to assess energy use and emissions associated with real-world driving, including the effects of road grade. This need is especially great as the electrification of the passenger vehicle fleet (from HEVs to PHEVs to BEVs) increases in response to climate and e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(12 citation statements)
references
References 39 publications
0
11
0
Order By: Relevance
“…Since 1999, a great number of studies have applied the conventional VSP equation and coefficients for LDV to estimate the driving power of passenger cars regardless of vehicle model and technology. VSP has been utilized to estimate driving power to construct fuel-consumption and -emission models, and conduct further analysis on the influential factors or contributors to vehicle fuel consumption [1,3,[7][8][9][10][11][12][13][14][15][16][17][18][19]. Nevertheless, before implementing the VSP equation and the LDV coefficients, none of them has performed validation to confirm prediction accuracy of whether the equation and coefficients estimated by the vehicles from the last 20 years can still accurately capture a vehicle or studied vehicle fleet.…”
Section: Introductionmentioning
confidence: 99%
“…Since 1999, a great number of studies have applied the conventional VSP equation and coefficients for LDV to estimate the driving power of passenger cars regardless of vehicle model and technology. VSP has been utilized to estimate driving power to construct fuel-consumption and -emission models, and conduct further analysis on the influential factors or contributors to vehicle fuel consumption [1,3,[7][8][9][10][11][12][13][14][15][16][17][18][19]. Nevertheless, before implementing the VSP equation and the LDV coefficients, none of them has performed validation to confirm prediction accuracy of whether the equation and coefficients estimated by the vehicles from the last 20 years can still accurately capture a vehicle or studied vehicle fleet.…”
Section: Introductionmentioning
confidence: 99%
“…In the past decades, a number of researchers have been applying vehicle fuel consumption models to transportation research such as prediction and analysis. The conventional approach of vehicle fuel consumption modeling consists of two main processes, which are vehicle driving power estimation, and fuel consumption and driving power relationship construction [2,[7][8][9][10][11][12][13][14][15]. In 1999, Jiménez et al [16] derived an equation for vehicle driving power estimation, and also provided a set of coefficients specified for light-duty vehicles' (LDVs) application called vehicle-specific power (VSP).…”
Section: Introductionmentioning
confidence: 99%
“…The equation simply requires data that can be observed from outside of the vehicles, such as speed, acceleration, road grade, and wind speed. Furthermore, a large number of researchers adopting VSP in their research have reported on the monotonically increasing relationship between VSP and fuel consumption [2,[7][8][9][10][11][12][13][14][15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…New government regulations have demanded an increase in automotive fuel economy (MPG-miles per gallon) to reduce dependency on imported oil for transportation [1,2]. This not only pushed automotive manufacturers to improve the efficiency of the powertrain design, but they also had to consider improving other components and systems in the vehicle.…”
Section: Introductionmentioning
confidence: 99%